Pembuatan Nitroselulosa Dari Selulosa Hasil Pemurnian Pelepah Sawit dengan Hidrogen Peroksida (H2O2) Sebagai Bahan Baku Pembuatan Propelan - Saragih E; Padil Padil; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Nitrocellulose is a polymer used as materials for propellant. Manufacture of nitrocellulose done with cellulose nitration process. Nitration of cellulose is a reaction force substitution or replacement of H+ from –OH- groups in cellulose contained in the NO2+ cluster of nitric acid (HNO3). Cellulose to be used is sourced from waste palm midrib. The purpose of this study is to obtain the best conditions of temperature and time nitration that α- cellulose nitration process to produce nitrocellulose with a high nitrogen content. Palm midrib cellulose purified before entering the nitration process. Stages of the purification process a palm midrib cellulose is extraction, hydrolysis, delignification and purification with hydrogen peroxide (H2O2). After the purification process, the next step is the process of nitration of cellulose with a mixture of nitric acid and sulfuric acid. Nitration process is done with the variation of temperature and reaction time. Nitrocellulose nitrogen levels will be analyzed with Fourier Transform Infra Red Spectroscopy (FTIR). The best conditions in the nitration process took 30 minutes with the temperature of 90 oC. Nitrogen levels were estimated on nitrocellulose > 12% so it can be used as raw material for the manufacture of propellants. Keywords: FTIR, Nitration, Nitrocellulose, Palm Midrib, Propellants